Respuesta :

        -7x - 2y = -13
-7x + 7x - 2y = 7x - 13
               -2y = 7x - 13
                -2         -2
                 y = -3.5x + 6.5

                      x - 2y = 11
    x - 2(-3.5x + 6.5) = 11
x - 2(-3.5x) - 2(6.5) = 11
             x + 7x - 13 = 11
                   8x - 13 = 11
                       + 13 + 13
                          8x = 24
                           8      8
                            x = 3

y = -3.5x + 6.5
y = -3.5(3) + 6.5
y = -10.5 + 6.5
y = -4
(x, y) = (3, -4)
ACCESS MORE